PENGARUH PENGHARGAAN INTRINSIK DAN PENGHARGAAN EKSTRINSIK TERHADAP KEPUASAN KERJA DAN KOMITMEN TENAGA PENDIDIK SEKOLAH MENENGAH KEJURUAN (SMK) DI KECAMATAN PANDAAN KABUPATEN PASURUAN - Ruslita Nur Aini; Muhammad Firdaus; Zainollah Zainollah (STIE Mandala Jember, 2017)
Rewardwas an honorarium or a remuneration which is accepted by someone depend on his job that has done. Reward was divided into two types, the first one was intrinsic reward, and the second one was extrinsic reward. Intrinsic reward was a reward which derived from the internal of someone. Extrinsic reward was a reward which derived from the external of someone. Theoretically, reward could give an effect on job satisfaction and individual commitment. Job satisfaction is a reflection of what was want from the job and what was received from the job. Commitment is a condition which individuals become bounded and involved by its activities and keep retaining the activities and the involvements. The purpose of this research was to study the effect of intrinsic reward and extrinsic reward on job satisfaction and commitment to vocational high school educators in Pandaan district Pasuruan regency. The types of this research was explanative research and using primary and secondary data collecting methods. Results of this research was reward, both intrinsic and extrinsic reward, had a direct, positive, and significant effect on job satisfaction and commitment to vocational high school educators in Pandaan district Pasuruan regency. Besides, job satisfaction also had a direct, positive, and significant effect on commitment to vocational high school educators in Pandaan district Pasuruan regency. Data analysis methods that used in this research was descriptive statistic analysis and inferential statistic analysis with path analysis. Based on the results, it is expected to vocational high school in Pandaan district Pasuruan regency could give more priority to improved the reward, both intrinsic and extrinsic reward by improved the job satisfaction, so that the commitment of educators also could be improved.